2007
DOI: 10.1137/060664483
|View full text |Cite
|
Sign up to set email alerts
|

Creep, Recovery, and Waves in a Nonlinear Fiber-Reinforced Viscoelastic Solid

Abstract: We present a constitutive model capturing some of the experimentally observed features of soft biological tissues: nonlinear viscoelasticity, nonlinear elastic anisotropy, and nonlinear viscous anisotropy. For this model we derive the equation governing rectilinear shear motion in the plane of the fiber reinforcement; it is a nonlinear partial differential equation for the shear strain. Specializing the equation to the quasistatic processes of creep and recovery, we find that usual (exponential-like) time grow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…An anisotropic viscoelastic model involving neo-Hookean isotropic and the standard reinforcing model anisotropic energy density components, (2.9) (b¼0) and (2.14), with an additional anisotropic viscous constitutive term, was considered in [16].…”
Section: Constitutive Relationsmentioning
confidence: 99%
“…An anisotropic viscoelastic model involving neo-Hookean isotropic and the standard reinforcing model anisotropic energy density components, (2.9) (b¼0) and (2.14), with an additional anisotropic viscous constitutive term, was considered in [16].…”
Section: Constitutive Relationsmentioning
confidence: 99%
“…For an incompressible material we now define eight independent invariants of the two tensors B and D by I 1 = tr B, I 2 = tr (B −1 ), I 5 = tr (DB), I 6 = tr (DB 2 ), I 7 = tr (D 2 ), I 8 = tr (D 2 B), I 9 = tr (D 2 B 2 ), I 10 = tr (D 3 ), (10) noting that the invariants I 3 = det B = 1 and I 4 = tr D = 0 have been omitted from the list by virtue of ( 6) and (8).…”
Section: Basic Equations 21 Kinematicsmentioning
confidence: 99%
“…Antman and Seidman [1] provided a detailed mathematical study of large shearing motions of nonlinearly viscoelastic slabs (see also Rajagopal and Saccomandi [27] for some exact solutions in a similar framework). Recently, Hayes and Saccomandi [21,22,23] and Destrade and Saccomandi [8,9,10] obtained some results for finite amplitude motions and waves in some classes of nonlinear viscoelastic materials. Earlier, Hayes and Rivlin [16,17,18,19,20] had established some general results for the theory of small motions superposed on a large deformation in nonlinear viscoelastic solids (see also a recent note by Saccomandi [28] concerning such waves in a special class of materials).…”
Section: Introductionmentioning
confidence: 99%
“…These simplifications of the general theory are not dictated by a rational methodology of investigation but only by empirical considerations or computational simplifications. A compromise between the complexity of the general theory in Merodio [7] and the specificity of the various particular models as in Anssari-Benam et al [8] or Destrade and Saccomandi [10] may be indicated by the isotropic model (1), i.e., by the mix between the classic theory of hyperelasticity and the Navier-Stokes theory.…”
Section: Introductionmentioning
confidence: 99%